Receptors Responsive to Protein Breakdown Products in G-Cells and D-Cells of Mouse, Swine and Human - Haid, Désirée C.; Jordan-Biegger, Constanze; Widmayer, Patricia; Breer, Heinz (Frontiers in Physiology, 2012)
Monitoring the luminal content in the stomach is of vital importance for adjusting the gastric activities, including the release of gastric hormones such as gastrin. Our previous studies have shown that in mice the gastrin-secreting G-cells express receptor types which are responsive to amino acids. Since the pig is considered as more suitable model for studying gastro-physiological aspects relevant for men, in this study we have analysed the distribution of G-cells and D-cells in the gastric antrum of men, swine and mouse and the expression of receptor types which may render these cells responsiveness to protein breakdown products. The results indicate that the number of G-cells per antral invagination was significantly higher in swine and human compared to mice and also the distribution pattern for G-cells differed between the species. The molecular phenotyping revealed that the receptors GPRC6A and CaSR were also expressed in G- and D-cells from swine and men. In the course of this study, an additional receptor type was found to be expressed in G- and D-cells, the peptone-receptor GPR92. This receptor type may be particular suitable for sensing protein breakdown products and thus be a key element to adjust the activity of G-cells and D-cells according to the progress of the digestive processes in the stomach. In search for elements of an intracellular signaling cascade it was found that G-cells express the G-protein subunits Gαq and Gαi2, as well as the phospholipase C subtype PLCβ3. In contrast, D-cells expressed the subtype PLCβ2 and neither Gαq nor Gαi2. These results indicate that there are significant species differences concerning the number and distribution pattern of gastric endocrine cells. However, the molecular phenotype of G-cells and D-cells appears to be similar in the three species.